Web-Based IT Service Management (ITSM) Design and Implementation for Ticketing Documentation and Troubleshooting - Rafin Simanjuntak; Mario Iskandar (Universitas Batanghari Jambi, 2026)
The purpose of this research is to develop a Web-Based IT Service Management (ITSM) system that facilitates centralized ticket handling and troubleshooting documentation. The system is implemented using the Python Django framework with SQLite as its database. To improve fairness and efficiency in task allocation, a request-based assignment mechanism has been implemented, allowing technicians to select and manage their own tickets. The system offers several key features, including role-specific dashboards, a real-time performance monitoring dashboard for technicians, repair logs, notifications for every ticket status update, and articles collectively referred to as a knowledge base that serve as a guide for users. The implementation of this ITSM solution is expected to overcome existing limitations within the IT support unit, accelerate problem resolution in accordance with service level agreements (SLAs), and generate accurate performance data to support future evaluations and continuous improvement of IT services.